The effectiveness of combining the type of implicit questions and their presentation density in an adaptive digital Assessment environment on reducing electronic stress and electronic test anxiety among educational technology and computer students - Elbradei, Ashraf Mohamed Mohamed; Abdelaal, Mohamed Abdelrahman Abdelmonem; El-Okkiah, Amira Ahmed fouad Hassan (Journal of Posthumanism, 2023)
The current research aims to know the effectiveness of combining the type of implicit questions (open/closed) and the density of question presentation (single/multiple) in an adaptive digital Assessment environment to reduce electronic stress and reduce electronic test anxiety among educational technology and computer students.To achieve this goal, a digital Assessment environment was applied to the research sample, which consisted of (60) first-year students in the Department of Educational Technology and Computer Science at the Faculty of Specific Education, Kafr Elsheikh University. They were distributed into four main groups, each group having (15) students, A group using the implicit question type (open) and the presentation density (single), a group using the implicit question type (closed) and the presentation density (single), a group using the implicit question type (open) and the presentation density (multiple), and a group using the implicit question type (closed) and the presentation density (multiple) when using electronic tests, according to the variables of the current research.The electronic stress and electronic test anxiety scale was applied pre-test to the research sample, to know the level of students, and these scales were applied post-test to the students. The results indicated that the combination of the type of implicit questions (open-closed) and the density of their presentation (single-multiple) in the adaptive digital Assessment environment reduced electronic stress and electronic test anxiety in favor of the interaction between the type of questions (closed) and the density of their presentation (single-multiple).